Motivation's Mediating Role in HR Information System , Career Development, and Employee Performance.: Peran Mediasi Motivasi dalam HR Information System, Pengembangan Karier, dan Kinerja Karyawan - Ahmad Rivaldi Mareyza; Sumartik (Universitas Muhammadiyah Sidoarjo, 2024)
This quantitative study aims to examine the influence of HR Information System (HRIS), career development, and organizational commitment on employee performance, with motivation as an intervening variable. The research population consists of 147 employees, with a sample of 60 selected using simple random sampling. Data collection employed questionnaires and interviews, with data analysis conducted using SmartPLS 3.2.8 software. The path analysis revealed that HRIS significantly affects employee performance, while career development and organizational commitment do not. HRIS and career development significantly influence motivation, while organizational commitment does not. Moreover, motivation significantly impacts employee performance. Notably, HRIS and career development have a significant impact on employee performance through motivation as an intervening variable, whereas organizational commitment does not have a significant influence on employee performance through motivation as an intervening variable. This study underscores the pivotal role of motivation in enhancing employee performance and provides valuable insights for organizations seeking to optimize their HR practices. Highlights: HR Information System's significant impact on employee performance. Motivation's pivotal role as an intermediary in the relationship between HRIS, career development, and employee performance. Insights for optimizing HR practices in organizations. Keywords: HR Information System, Career Development, Organizational Commitment, Motivation, Employee Performance